Ambedkar on law, constitution, and social justice - Shabbir, Mohammad (Jaipur : Rawat Publications, 2005)
Contributed articles.
Includes bibliographical references.
Keywords: SOCIAL JUTICE; CONSTITUTIONAL LAW